A família para além do gênero: reformulações dos direitos reprodutivos a partir das biotecnologias - Laís Godoi Lopes (2019)
This thesis investigates the intersection between Law, Gender and Family, based on the question of the limits and possibilities imposed to the reproductive technologies. For this, it aims to contextualize historically, from a feminist perspective, the emergence of the reproductive sciences in a context of growing social medicalization. Driven by social actors linked to eugenic, neo-Malthusian and population-controlled movements, conception and contraception have a spurious history yet to be rescued. Subsequently, the characterization of reproduction as a power dispositif in the Foucauldian sense, governed by a neoliberal governmentality and able of engendering specific subjectivities. A relevant dimension of the device is the regulation that establishes eligibility criteria: through it, it is decided which arrangements are considered socially adequate for reproduction. The models and normative experiences of regulation of medically assisted reproduction are analyzed. This analysis reveals the exclusionary operation of social norms that constitute the family ideal: the heteronormative matrix, the traditional family ideal, the ambivalence of motherhood and the protection of child sexual innocence. Criticism of these norms allows making visible and conferring discursive existence of alternative reproductive experiences and demands. A more pertinent framework of these realities lies in the notion of reproductive justice. Moreover, recognition of the interdependence and precariousness constitutive of human experience becomes an essential starting point for political demands for freedom, including reproductive freedom and the constitution of families.